Ecotoxicological assessment of activated sludge - Angulo Maya, Robert Steve (2022)
Ecotoxicology was born from the need to avoid problems of large-scale environmental contamination by toxins; as it has progressed, it has been solving problems since in a techno-industrial society governed by consumption. Ecotoxicology is a necessary discipline to reflect on the costs and benefits of technological and industrial decisions. The mining industry and its notable boom make bioassays required to verify the environmental impacts that drilling can cause, the release of sediments into the environment. This mining project features a number of valuable metals; therefore, they will be present in the drilling muds that make it up. The release of discharge water from the purification processes of the wastewater treatment plants in the camps. The objective of this work is to analyze bioassays of the drilling sediments from well "D" and well "R", the wastewater from "Camp X" and "Camp Y", to verify if they affect the living beings of the ecosystem in the case that there is no proper disposal and final treatment. To verify the toxicity of sludge and sediments, germination tests were carried out at 72 hours using lettuce-radish seeds, seedling development to verify inhibition, and the presence of abnormalities at 10 and 20 days. Pseudomonas spp. were inoculated in solid and liquid medium to verify the existence of inhibition at different concentrations of drilling sediments. Fungal inhibition tests were performed by seeding soil dilutions on potato dextrose agar and subjecting the soil fungi to varying concentrations of drilling sediments and sewage sludge.